On the Putnam-Fuglede theorem - Yin Chen (International Journal of Mathematics and Mathematical Sciences)
We extend the Putnam-Fuglede theorem and the second-degree Putnam-Fuglede theorem to the nonnormal operators and to an elementary operator under perturbation by quasinilpotents. Some asymptotic results are also given.